FAKTOR-FAKTOR BEBAN KERJA YANG MEMPENGARUHI KINERJA PEGAWAI KANTOR PERTANAHAN KOTA AMBON - Agusthina Risambessy (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2019)
The performance of an institution depends not only on the capabilities possessed by employees but also influenced by various factors including the work environment that provides comfort, the large volume of work that must be completed and the work discipline that must be obeyed by each employee. This study seeks to analyze and explain the factors of non-physical work environment, workload and work discipline on employee performance. The objects studied were 62 employees who were sampled at the Land Office. The sampling technique is sampling census data. By using multiple regression analysis. The results of the study prove that the non-physical work environment has a significant positive effect on employee performance, workload has a significant effect on employee performance and work discipline has a significant effect on employee performance. Environmental factors Non-physical work has a very dominant influence in improving performance. It is clear that working relationships between employees need to be a top priority in completing work. For the next researcher, it is recommended to be able to examine environmental factors as a whole.